APPLICATION OF REMOTE SENSINGTECHNIQUES IN PETROLEUM EXPLORATION : THE INDONESIAN EXPERIENCE - B. Situmorang (Scientific Contributions Oil and Gas, 1991)
Since the seventies, remote sensing data have been widely used in petroleum exploration in Indonesia. These include Landsat. Spot and Radar imageries, apart from the conventional aerial photographs. Examples from Nias Island, East Kalimantan Basin and Irian Jaya, will be presented to show the extensive application of remote sensing techniques in general geological mapping and hydrocarbon exploration.